2018
DOI: 10.1175/jcli-d-17-0196.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Dependence of Coupling between Storm Tracks and Sea Surface Temperature in the Southern Hemisphere Midlatitudes: A Statistical Assessment

Abstract: Two-way coupling between sea surface temperature (SST) variations in the midlatitude southern oceans and changes of synoptic-scale (2–8 day) eddy activities in the lower and upper troposphere throughout the year is investigated based on lagged maximum covariance analysis using reanalysis datasets from 1951 to 2000. Results show a strong seasonal dependence of the coupling, as characterized by the most prominent one in austral midsummer (January). On one hand, SST variations in austral late spring (primarily Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 46 publications
3
9
0
1
Order By: Relevance
“…We demonstrate how a poleward shift of the large-scale synoptic features that dominate the Southern Hemisphere midlatitude meteorological variability (in particular the jet-stream and stormtracks) imposed a dramatic rainfall shortage in SW South Africa. Although the very strong 2015-2016 El Niño event occurred during the ongoing drought in the Cape Town area, and may therefore have contributed to the exceptional increase in global and regional temperatures during these three years, the feedback between SSTs and atmospheric dynamics (particularly ENSO) on winter rainfall in the region is far less clear than for the summer rainfall region of South Africa (Reason et al 2002, Philippon et al 2012, Zhang et al 2018. Results here show a strong SAM influence together with an expansion of the semi-permanent subtropical anticyclones in the South Atlantic and South Indian Oceans as key factors for a poleward deviation of moisture corridors, and consequently for the regional drying trend which culminated in the 'Day Zero' water crisis.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…We demonstrate how a poleward shift of the large-scale synoptic features that dominate the Southern Hemisphere midlatitude meteorological variability (in particular the jet-stream and stormtracks) imposed a dramatic rainfall shortage in SW South Africa. Although the very strong 2015-2016 El Niño event occurred during the ongoing drought in the Cape Town area, and may therefore have contributed to the exceptional increase in global and regional temperatures during these three years, the feedback between SSTs and atmospheric dynamics (particularly ENSO) on winter rainfall in the region is far less clear than for the summer rainfall region of South Africa (Reason et al 2002, Philippon et al 2012, Zhang et al 2018. Results here show a strong SAM influence together with an expansion of the semi-permanent subtropical anticyclones in the South Atlantic and South Indian Oceans as key factors for a poleward deviation of moisture corridors, and consequently for the regional drying trend which culminated in the 'Day Zero' water crisis.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…We first examined whether the coupling between storm-track activity and SSTAs (refer to Z20) can be reproduced in the ERA-Interim (1979-2018. The lagged MCA is applied as a function of 850-hPa v′T′ and SSTAs in the SH midlatitudes (30°-60°S, 0°-360°E) (hereinafter, the SH-MCA).…”
Section: Sic Responsementioning
confidence: 99%
“…Particularly, synoptic‐eddy vorticity fluxes, closely linked to storm‐track activity, act to convert the response of atmospheric circulation from baroclinic to equivalent barotropic and amplify it downstream (Deser et al., 2007). Our previous studies have suggested that SST variation in the western SA frontal zone has predominant influence on the hemispheric storm‐track activity in austral summer (Zhang et al., 2018, 2020, hereinafter Z20). Hence, we hypothesize that the SA SST variation can lead to the planetary‐scale atmospheric response through synoptic‐eddy feedback on the time–mean flow, and in turn imprint on Antarctic summer sea ice.…”
Section: Introductionmentioning
confidence: 99%
“…To quantify influences of the Kuroshio on the marginal seas, we conduct the lagged maximum covariance analysis (MCA), which has been widely used in the previous studies regarding the midlatitude ocean-atmosphere interaction (e.g., Frankignoul 1999, 2002;Wu 2013, 2015;Zhang et al 2018). The MCA isolates pairs of spatial patterns that maximize their covariance and the associated time coefficients by performing a singular value decomposition of the covariance matrix between two fields.…”
Section: Statistical Toolsmentioning
confidence: 99%